A contribuição da linguística textual e da teoria da relevância para o processo de inferenciação em textos publicitários - NASCIMENTO, Rosana Carmen Pinto do (Universidade Federal do Pará, 2012)
This work presents a descriptive analysis based in a corpus constituted by 50 publicity texts, which main objective is to verify how cognitives strategies are processed, since they are crucial to the textual understanding and also to the meaning elaboration, here in narrow sense named inference. As communicative human activities come from ways which are intregatives and unseparated: the emissor, the text and receptor, this work tries to establish the role of each one of those elements plays to inference, based in the theoretical frames of two Linguistics branches: 1) Textual Linguistics which takes the text in detail to enfatize what cognitive activities are used, as inference; 2)Pragmatics, which comes along to Textual Linguistics, with special attention to the Relevance: Communication and cognition of Sperber and Wilson (1986), searching for relevant considerations about the way the information is represented in the mind as well how it is inferencially processed.